The Effect of Number of Population, HDI And Unemployment Rate on Poverty Level in Banten 2017-2020: Pengaruh Jumlah Penduduk, IPM dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan di Banten Tahun 2017-2020 - Nurcholis, Achmad Fauzan Zain Ardhi; Setyowati, Eni (Procedia of Social Sciences and Humanities, 2022)
This research is motivated by the case of poverty in Banten Province which is still relatively high on the island of West Java. The purpose of this study was to analyze and determine the effect of the level of population, the Human Development Index (HDI) and the unemployment rate on the poverty level in Banten Province. This observation uses secondary data obtained from the Central Statistics Agency (BPS) Banten and Indonesia. The technique used is a quantitative approach with panel data regression techniques from 2017-2020 with a total of 8 regencies/cities of observation data and processed with a Fixed Effect Model (FEM) approach using Eviews 8. The final calculation results show that the Population variable and the Human Development Index has a negative effect on poverty, and Unemployment has a significant effect on Poverty in Banten Province in 2017-2020. This research is expected to be taken into consideration in decision making for the central and local governments in dealing with the problem of poverty in Banten Province.